Die Digitalisierung der Hauptversammlung Die Digitalisierung der Hauptversammlung - Wunderlich, Samuel Matthias (Schriften zum Gesellschafts-, Bank- und Kapitalmarktrecht, 2022)
The digitization of the Annual General Meeting is progressing inexorably. A return to the analog age of purely face-to-face meetings is inconceivable after the experience with the virtual AGM during the COVID-19-pandemic. A lively discourse has flared up on the question of how to shape the digitization process in legislative terms. This paper makes an innovative contribution to this discourse by presenting a consistent proposal for the continuation of the virtual shareholders' meeting and the implementation of a process shareholders' meeting in the German Stock Corporation Act (AktG).